2021
DOI: 10.1177/1059601121998892
|View full text |Cite
|
Sign up to set email alerts
|

Does Having a Critical Mass of Women on the Board Result in More Corporate Environmental Actions? Evidence From China

Abstract: Arguments based on ethical sensitivity differences, gender-based functional differences, and gender discrimination suggest that having more women on the board of directors improves corporate environmental actions (CEA). However, empirical evidence of this relationship has provided inconsistent results. To explore this inconsistency, we draw on critical mass theory to examine how women on boards influence CEA. Using a sample of Chinese listed firms during 2010–2016, we find that firms with a critical mass of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 69 publications
0
23
0
2
Order By: Relevance
“…Studies related to board GD drawing on CMT suggest that female directors may have a voice on the board only when they hold considerable number of seats on board (Gong et al, 2021; Torchia et al, 2011). A similar result was suggested in the context of the role of females in corporate strategic decisions (Konrad et al, 2008).…”
Section: Theoretical Perspective and Literature Reviewmentioning
confidence: 99%
“…Studies related to board GD drawing on CMT suggest that female directors may have a voice on the board only when they hold considerable number of seats on board (Gong et al, 2021; Torchia et al, 2011). A similar result was suggested in the context of the role of females in corporate strategic decisions (Konrad et al, 2008).…”
Section: Theoretical Perspective and Literature Reviewmentioning
confidence: 99%
“…By using Bloomberg data from 2011-2019 for French stock exchange companies and environmental disclosure data, it was indicated that higher percentage of female board members related to higher sustainability disclosure (Chebbi et al, 2020). In addition, from China, Gong et al (2021) found, using information from Chinese stock echange firms from 2010-2016, that boards with at least three female members showed increased quality and speed as regards to environmentally related initiatives.…”
Section: Women On Boards and Sustainability Reportingmentioning
confidence: 99%
“…The second most analyzed topic is the relationship between women’s presence on corporate boards and corporate social responsibility (Biswas et al , 2021; Dang et al , 2021; Mansoor and Ali, 2018). Other studies analyzed the boards’ strategic control (Nielsen and Huse, 2010), corporate sustainability (Galbreath, 2011), corporate governance (Abdullah et al , 2016), efficiency (Ramly et al , 2017), corporate reputation (Inamdar and Nagendra, 2017), corporate environmental actions (Gong et al , 2021), effects on agency costs (Amin et al , 2021), cost of debt (Kamil and Appiah, 2021), adoption of the United Nations Sustainable Development Goals (Cicchiello et al , 2021) and employer attractiveness (Schäpers et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%